Effect of Sr addition on porosity formation in directionally solidified A356 alloy. (1st August 2013) - Liao, H C; Song, W; Wang, Q G; Zhao, L; Fan, R; Jia, F
Abstract : Porosity formation in a Sr modified A356 alloy was investigated using microfocus X-ray imaging and directional solidification technology. In situ experimental results indicate that Sr addition enhances the effectiveness of oxide inclusions in the liquid aluminium alloy as pore nucleation sites and thus leads to a remarkable rise in the nucleation temperature. As pores are nucleated in high temperature region and far away from the solidification front, they can grow at a high growth rate for a relatively long time, and thus, significant increases in the volume fraction of porosity and particularly the number density of large pores are seen in the Sr modified alloy. The growth rate of pores decreases with the reduction in local liquid temperature, and it fluctuates violently during directional solidification. Addition of Sr weakens this fluctuation and decreases the average growth rate of pores. Addition of Sr has a considerable influence on the size distribution of pores.